Analisis Rendahnya Literasi Dasar Siswa Kelas 2 SDN Kalibeluk 02 - Salsabila, Riska Zabrina; Kusumawati, Dian; Wuryani, Meilan Tri (Universitas Muhammadiyah Magelang, 2024)
Basic literacy is an important skill that all students should have, especially those at the primary education level. This study raises the problem of the low reading and writing skills of grade 2 students at SDN Kalibeluk 02, namely related to the causes and factors that affect their basic literacy development. The purpose of this study is to examine the basic literacy problems faced by grade 2 students at SDN Kalibeluk 02 and to identify solutions in the form of factors that contribute to improving students' literacy skills and methods to overcome these problems. This research utilized a qualitative approach involving data collection through observations, interviews and documentation studies. As shown by the results of the study, students have difficulty reading, writing and understanding simple texts. Some of the facts obtained towards the problem are low interest in learning, lack of interesting teaching materials, and lack of support from families especially parents during learning at home. This study suggests that literacy improvement efforts should involve students themselves, parents and teachers to create a better learning environment. It is hoped that with attention to these issues, students will acquire the most effective basic literacy skills and support their learning process in the future.